Un-Sounding: A New Method for Processing Non-linguistic Poetry. - Smith, Kristen (English Studies in Canada)
The article focuses on a new method called "un-sounding" for analyzing non-linguistic poetry. The method examines the works of three poets Mary Ellen Solt, Caroline Bergvall and Eric Schmaltz, who communicate meaning through sound and its absence, challenging traditional methods of reading and viewing.